2008
DOI: 10.1038/sj.bjc.6604395
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing treatment decision-making: pilot study of a treatment decision aid in stage IV non-small cell lung cancer

Abstract: We developed a decision aid (DA) for patients with metastatic non-small cell lung cancer (NSCLC), to better inform patients of their prognosis and treatment options, and facilitate involvement in decision-making. In a pilot study, 20 patients with metastatic NSCLC attending outpatient clinics at a major cancer centre, who had already made a treatment decision, reviewed acceptability of the DA. The median age of the patients was 61 years (range 37 -77 years), 35% were male, 20% had a university education, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 28 publications
4
46
1
Order By: Relevance
“…21,29 They were also similar to those found for other pilot studies of DAs in advanced cancer from other countries. [9][10][11][12]30 The main conceptual frameworks of SDM and action science both emphasize the joint nature of significant medical decisions-that neither doctor not patients can make and implement these decisions alone. To accomplish this requires shared understanding of the situation, the goals, and the choices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,29 They were also similar to those found for other pilot studies of DAs in advanced cancer from other countries. [9][10][11][12]30 The main conceptual frameworks of SDM and action science both emphasize the joint nature of significant medical decisions-that neither doctor not patients can make and implement these decisions alone. To accomplish this requires shared understanding of the situation, the goals, and the choices.…”
Section: Discussionmentioning
confidence: 99%
“…Other small trials of DAs in advanced cancer have all found very high rates of patient preference for participation in decisions. 9,10,12,30 There was a significant gap between patients' desired role and their actual role in decisions, with patients generally having less involvement in decisions than desired. The results were similar when restricting the analysis to only those patients who had made a decision during the study period (results not presented).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Patients with advanced cancer who have poor illness understanding and overestimate their prognosis are more likely to choose aggressive medical care at the end of life. 17 Moreover, in an investigation of 181 patients with advanced cancer receiving palliative therapies, one JOURNAL OF CLINICAL ONCOLOGY third of participants reported an aim of treatment to be cure, both at the time of study entry and 12 weeks later. [13][14][15][16] Even when presented with accurate information about their diagnoses, patients with advanced cancer frequently retain inaccurate perceptions of their illness.…”
Section: Introductionmentioning
confidence: 99%
“…However, past studies have consistently shown that many patients with advanced cancer have inaccurate prognostic understanding [4,[8][9][10][11][12]. Accurate prognostic understanding is difficult for patients even when accurate information is provided by their treating physicians [13][14][15]. To improve patients' illness understanding, clinicians need to be aware of factors that could hamper patients' accurate illness understanding.…”
Section: Introductionmentioning
confidence: 99%